2009
DOI: 10.1590/s0100-40422009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Composição volátil dos defeitos intrínsecos do café por CG/EM-headspace

Abstract: Recebido em 23/1/08; aceito em 29/9/08; publicado na web em 5/2/09 VOLATILE cOmpOsITION OF INTRINsIc DEFEcTIVE cOFFEE BEANs By Gc/ms-hEADspAcE. About 20% of Brazilian raw coffee production is considered inappropriate for exportation. consequently, these beans are incorporated to good quality beans in the Brazilian market. This by-product of coffee industry is called pVA due to the presence of black (p), green (V) and sour (A) defective beans which are known to contribute considerably for cup quality decrease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
9
0
7
Order By: Relevance
“…The compounds suggested as possible markers for defective seeds were benzene acetic acid (methyl ester), 2‐isoamyl‐6‐methylpyrazine, 1H‐pyrrole, 4‐methylthiazole, and 1,5‐dimethyl‐2‐pyrrolecarbonitrile, demonstrating that the presence of these compounds in the volatile fraction could be used to distinguish between healthy and defective coffee seeds. Following research conducted in Brazil, several papers were published concerning the identification of volatile markers of defective seeds (Toci and Farah , ; Bandeira and others ). In these studies, it was found that defective seeds contained a greater range and higher concentrations of volatile compounds compared to healthy seeds.…”
Section: Defective Seeds and Types Of Beveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds suggested as possible markers for defective seeds were benzene acetic acid (methyl ester), 2‐isoamyl‐6‐methylpyrazine, 1H‐pyrrole, 4‐methylthiazole, and 1,5‐dimethyl‐2‐pyrrolecarbonitrile, demonstrating that the presence of these compounds in the volatile fraction could be used to distinguish between healthy and defective coffee seeds. Following research conducted in Brazil, several papers were published concerning the identification of volatile markers of defective seeds (Toci and Farah , ; Bandeira and others ). In these studies, it was found that defective seeds contained a greater range and higher concentrations of volatile compounds compared to healthy seeds.…”
Section: Defective Seeds and Types Of Beveragesmentioning
confidence: 99%
“…The compounds γ‐butyrolactone, hexanoic acid, β‐linalool, and 2‐butyl‐3,5‐dimethylpyrazine were identified as markers for defective seeds in general (Toci and Farah , ). Among the different defects, black defect was associated with the specific marker compounds 3‐ethyl‐2‐methyl‐1,3‐hexadiene, 2‐methylpyrazine, 2‐furylmethanol acetate, and 2‐pentylfuran (Bandeira and others ; Toci and Farah ). Additional compounds suggested as low‐quality indicators were 2,3,5,6‐tetramethylpyrazine, 2,3‐butanediol, 4‐ethylguaiacol*, β‐linalool, 2,3‐dimethylbutyl butanoate, 2‐phenylethyl acetate, 2,3‐butanedione*, hexanedioic acid, guaiacol*, 2,3‐dihydro‐2‐methyl‐1H‐benzopyrrole, 3‐methylpiperidine, 2‐pentylpiperidine, 3‐octen‐2‐one, 2‐octenal, 2‐pentylfuran, and 2‐butyl‐3‐methylpyrazine (Toci and Farah ).…”
Section: Defective Seeds and Types Of Beveragesmentioning
confidence: 99%
“…This also suggests that early hulling did not favor the production of coffee with these defects because the early-hulled coffee presented equal or lower values of electrical conductivity and potassium leaching than later-hulled coffee (Table 2). According to Bandeira et al (2009), green and green black coffee beans contain chemical compounds that are not found in higher quality coffees, which may be associated with the lower quality of the product. They also exhibited lower quality, undesirable acidity and oxidation .…”
Section: Resultsmentioning
confidence: 99%
“…Trabalhos recentes relatam a sua utilização na discriminação de amostras de café torrado obtidas de frutos de diferentes estádios de maturação e tipos de processamentos pós-colheita através de sua composição volátil, 34 e a avaliação da composição volátil dos defeitos intrínsecos do café (preto, verde e ardido) para identificação de marcadores dos defeitos em relação aos grãos sadios. 35 A avaliação conjunta dos gráficos de escores (Figura 4) e pesos (Figura 5) mostra que os sinais da região entre 2800 e 3000 cm -1 e 1750 cm -1 foram os principais responsáveis pela discriminação das amostras de café com 0% de casca, uma vez que as informações sobre essas bandas e as amostras de café puro encontram-se em áreas equivalentes nos dois gráficos, ou seja, valores positivos em CP1 e CP2. Isso confirma a análise visual dos espectros da amostra de café sem adulterante e da casca pura após a torração (Figura 2), onde é verificada a presença dessas bandas apenas no espectro do café não adulterado.…”
Section: Resultados E Discussão Análises Por Espectroscopia No Infravunclassified